Teoria dos ciclos políticos e indicadores macroeconômicos: um estudo sobre os estados brasileiros - Regis, Salvio Delmas (Universidade Federal Rural do Semi-Árido, 2019)
The literature associated with political cycle theory points to the existence of manipulation of expenditures in electoral periods, especially regarding public expenditures that are better able to improve the image of the ruler and thereby have a positive influence on his or her electoral performance. Supported by this finding, this study aims to analyze whether political cycles affect macroeconomic indicators in the Brazilian states and the Federal District, from 2005 to 2016, comprising three electoral cycles. The sampling plan will be composed of the 26 states of the federation, besides the Federal District. In relation to time, the research will analyze and compare data for the period from 2005 to 2016. The analyzes aimed at macroeconomic indicators that contribute to the understanding of the market and the composition of the Gross Domestic Product (GDP), as is the case. The case of companies' gross revenues, wages paid to workers and the absolute number of employed persons, in order to verify how electoral years and the first term of office affected such indicators in the states and the Federal District in the Brazil, was also analyzed the behavior of the indicators in the case of states where members of the same political party as the President of the Republic are trying to elect for governor. The collected data were treated using the panel data econometric regression technique. For this, the macroeconomic indicators served as dependent variables and the independent variables of interest were presented in the form of models that indicate if the year is electoral, if the rulers. They are exercising their first term or if the rulers are in their first term and the year is electoral. The findings of the research indicate that the party coincidence between governors and President of the Republic increases the likelihood of reelection, suggesting the occurrence of political cycles. Regarding the other variables, however, it was found that political cycles do not affect, at levels of statistical significance, the macroeconomic indicators surveyed by the states and the Federal District.
Keywords: Administração pública; Ciclos políticos; Indicadores macroeconômicos; Public administration; Political cycles; Macroeconomic indicators; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA